Kea show three signatures of domain-general statistical inference - Amalia P. M. Bastos (Nature Portfolio, 2020)
Previously only humans and the great apes have been shown to use probabilities to make predictions about uncertain events, and integrate social and physical information into their predictions. Here, the authors demonstrate these capacities in a parrot species, the kea.